Аutosomal Dominant Oculodental-Digital Dysplasia with Mutation in Gene GJA1 (Clinical Case) - I. V. Zolnikova; V. V. Kadyshev; A. V. Marakhonov; S. I. Kutsev; R. A. Zinchenko (Oftalʹmologiâ, 2021)
The purpose: to describe clinical cases of oculodental-digital dysplasia (ODDD, OMIM #164200) with mutation in GJA1 (OMIM 121014) with molecular genetic verification of the diagnosis.Methods. The article describes the clinical case of oculodental-digital dysplasia in a 51 years old patient. Patient underwent full ophthalmic examination including autorefractometry, visual acuity testing with full correction, tonometry, biomicroscopy, fundus examination and photo as well as kinetic perimetry, autofluorescence and optical coherence tomography (OCT) of macula and optic disk were performed. Electrophysiological examination included Visual Evoked Potentials (VEP) to flash and pattern stimulation, ISCEV standard electroretinograms (ERG) and macular ERG. For the verification of the diagnosis and pathologic gene molecular genetic examination was performed with family anamnesis previously attained.Results. The patient was complaining the deterioration of vision, hearing loss and the sense of smell. Visual deterioration was associated with nyctalopia. Natural history revealed glaucoma 2а which was diagnosed when he was 48 years old. Best corrected visual acuity was 1,0. Peripheral visual field defects were revealed bilaterally. High visual acuity correlated with normal foveal structure on OCTs the retinal nerve fiber layer (RNFL) was thinner than normal in temporal half; deep excavation was visualized in both eyes. Normal MERG and bilateral decrease of scotopic, maximal full-field ERG was recorded which correlated with nyctalopia, as well as subnormal photopic responses indicating cone system involvement. The genetics revealed characteristic features of the face: a small nose with hypoplasia of the wings of the nose, unfolded nostrils and a wide bridge of the nose (pseudohypertelorism). On right-wing the ear sink was detected 2 antitraguses. Changes fingers upper extremities — operated syndactyly IV and V on the background of brachydactyly of the fingers. On the legs on both sides — syndactyly III–IV. 10 years the sense of smell has been dereriorated. In the study of DNA in proband in direct Sanger sequencing of all exons 1–2 and regions of exon-intron compounds of gene GJA1, was found the pathogenic variant in second exon c.412G>A (p.Gly138Ser) in heterozygous state. Was established autosomal dominant type of disease.Conclusion. We are the first to describe rod-cone dystrophy in oculodental-digital dysplasia.